2010
DOI: 10.1007/s00280-010-1380-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and cerebrospinal fluid pharmacokinetics of MP470 in non-human primates

Abstract: Although CSF penetration is minimal, MP470 has demonstrated potent activity against cancer cell lines in vitro and in vivo, and further clinical investigation is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Inhibitor 33 (MP470, amuvatinib) is structurally different from most of the MET inhibitors in Chart , as it has a piperazinyl ring to deliver the aryl group into the back pocket instead of a phenoxy group . Compound 33 is reported to be a multitarget tyrosine kinase inhibitor that has demonstrated in vitro and in vivo activity against multiple validated cancer targets including mutant KIT, mutant PDGFR, mutant FLT3, MET, and RET …”
Section: Met Small Molecule Inhibitorsmentioning
confidence: 99%
“…Inhibitor 33 (MP470, amuvatinib) is structurally different from most of the MET inhibitors in Chart , as it has a piperazinyl ring to deliver the aryl group into the back pocket instead of a phenoxy group . Compound 33 is reported to be a multitarget tyrosine kinase inhibitor that has demonstrated in vitro and in vivo activity against multiple validated cancer targets including mutant KIT, mutant PDGFR, mutant FLT3, MET, and RET …”
Section: Met Small Molecule Inhibitorsmentioning
confidence: 99%
“…It has been reported that MP‐470 is a multi‐targeted inhibitor of the receptor tyrosine kinases Flt3, c‐Kit, Axl, c‐Met, PDGFRα/β, and c‐Ret. 29 , 30 , 31 To identify which of these purported targets are expressed in our NSCLC cell‐lines, we first investigated their expression via RT‐PCR. We found that H460 cells expressed AXL, MET , and PDGFRβ mRNA, as did A549 cells with the inclusion of PDGFRα (Figure S3A ).…”
Section: Resultsmentioning
confidence: 99%
“…To better understand the mechanism by which MP‐470 inhibits cell proliferation, we investigated the expression of its targets and the downstream signalling pathways that contribute to this effect. It has been reported that MP‐470 is a multi‐targeted inhibitor of the receptor tyrosine kinases Flt3, c‐Kit, Axl, c‐Met, PDGFRα/β, and c‐Ret 29–31 . To identify which of these purported targets are expressed in our NSCLC cell‐lines, we first investigated their expression via RT‐PCR.…”
Section: Resultsmentioning
confidence: 99%
“…suggest that they display a higher preference for the oncogenic mutants over wild-type FLT3. (15). They are all rather nonspecific kinase inhibitors inhibiting a wide range of kinases.…”
Section: Targeting Receptor Ubiquitinationmentioning
confidence: 99%